Inca Food: Animal and Mineral - Coe, Sophie (Petits Propos Culinaires, 1988)
Sophie Coe, whose three-part essay on 'Aztec Cuisine' (PPC 19, 20, 21) evoked much interest, has now furnished us with an account of Inca foodstuffs. Unlike the Aztecs, the Inca had domesticated mammals; and this essay deals with all their animal foods- and some mineral ones as a tailpiece.